Comparing maternal postpartum hemorrhage outcomes with uterine balloon tamponade versus vacuum-induced hemorrhage devices: a retrospective cohort study - Leslie N. Chan; Albert Xu; Andrea Jelks (The Journal of Maternal-Fetal & Neonatal Medicine, 2025)
Objective To compare maternal postpartum hemorrhage outcomes between uterine balloon tamponade (UBT) and vacuum-induced hemorrhage control devices (VHD).Methods We conducted a retrospective cohort study of 184 deliveries using UBT with the Bakri® Postpartum Balloon or VHD with the JADA® System at an urban safety-net hospital in the United States between January 2018 and December 2023. The primary outcome was massive transfusion (≥4 units packed red blood cells [pRBCs]). Secondary outcomes included any blood product transfusion, quantitative blood loss (QBL), duration of hemorrhage control device, duration of urinary catheter postpartum, and device expulsion. Treatment failures were also assessed.Results Out of 184 cases using a hemorrhage control device, there were 130 cases using UBT and 54 cases using VHD. Outcomes were stratified by delivery type. No significant difference in massive transfusion was found between VHD and UBT groups for both vaginal (4/45 [8.9%] vs. 8/64 [12.5%], p = 0.76) and Cesarean deliveries (2/9 [22.2%] vs. 10/66 [15.2%], p = 0.63). In vaginal deliveries, VHD was associated with lower median QBL (2,046 mL [IQR: 1,604-2,324 mL] vs. 2,387 mL [IQR: 1,774-2,966 mL], p = 0.02), lower rates of pRBC transfusion (24/45 [53.3%] vs. 51/64 [79.7%], p = 0.01), and lower device expulsion rates (0/45 [0.0%] vs. 9/64 [14.1%], p = 0.02). No significant differences between the two PPH devices were noted in Cesarean deliveries in these outcomes. VHD had shorter indwelling device times compared to UBT in both vaginal and Cesarean deliveries (vaginal: 4.3 h [IQR: 2.8-8.6 h] vs. 13.7 h [IQR: 6.9-19.7 h], p < 0.001; Cesarean: 3.0 h [IQR: 2.1-4.9 h] vs. 13.6 h [IQR: 11.3-18.8 h], p < 0.01). Post-device urinary catheter duration was similar between devices.Conclusion No difference in massive transfusion rate was observed between VHD and UBT. VHD was associated with lower QBL, fewer transfusions, and shorter device indwelling times in vaginal deliveries but not Cesarean deliveries, though our study lacked power to detect significant differences between outcomes in Cesarean deliveries. Future research, including randomized controlled trials, is needed to further evaluate the clinical and cost-effectiveness of VHD compared to UBT.